THE CONCEPT OF WASAá¹¬IYYAH IN FIQH MUHAMMADIYAH PERSPECTIVE - Fitra, Tasnim Rahman; Putra, Devrian Ali; Desmanto, Sukma Nada (Asy-Syari’ah, 2022)
Abstract: This study discusses the concept of wasaá¹iyyah Muhammadiyah's perspective on fiqh problem development, especially in Indonesia. It is related to the internal conflicts of Muslims in various aspects of life, includingIslamic law or fiqh. These disputes are caused by the friction between the two opposing ideologies in methodology and approach, sometimes caused by an intervention born through contradiction between liberals who want to free themselves from the shackles of textual understanding from the conservative group. In this case, Muhammadiyah occurs to introduce itself as an organization that seeks to offer concrete solutions through its wasaá¹iyyah understanding. This study aims to reveal the concept of wasaá¹iyyah in Muhammadiyah fiqh, which is related to the expression of the wasaá¹iyyah idea in the fiqh produced by Muhammadiyah. This study uses a literature research method that focuses on wasaá¹iyyah concepts as seen from the understanding of Muhammadiyah fiqh through decisions, congress results or the other fiqh products officially issued by Muhammadiyah. This study concludes that the concept of fiqh wasaá¹iyyah Muhammadiyah tries to understand and place text and context proportionally to raise non-radical characteristics and also non-liberal. Furthermore, Muhammadiyah upholds the principle of tawÄsuá¹ which is combined with the codes of tawÄzun and ta'Ädul through an â€œIslam Berkemajuan" or the progressive Islam orientation.